2021
DOI: 10.3390/plants10051023
|View full text |Cite
|
Sign up to set email alerts
|

Regions of Chromosome 2A of Bread Wheat (Triticum aestivum L.) Associated with Variation in Physiological and Agronomical Traits under Contrasting Water Regimes

Abstract: Understanding the genetic architecture of drought tolerance is of great importance for overcoming the negative impact of drought on wheat yield. Earlier, we discovered the critical role of chromosome 2A for the drought-tolerant status of wheat spring cultivar Saratovskaya 29. A set of 92 single-chromosome recombinant double haploid (SCRDH) lines were obtained in the genetic background of Saratovskaya 29. The lines carry fragments of chromosome 2A from the drought-sensitive cultivar Yanetzkis Probat. The SCRDH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…This can be explained by the findings of Mathew et al (2019) who reported a root and shoot biomass association region on chromosome 1B. Further, Pshenichnikova et al (2021) found 53 QTL associated with physiological and agronomic traits under contrasting water supply. These findings may explain the importance of Q.ICD.11.…”
Section: Discussionmentioning
confidence: 94%
“…This can be explained by the findings of Mathew et al (2019) who reported a root and shoot biomass association region on chromosome 1B. Further, Pshenichnikova et al (2021) found 53 QTL associated with physiological and agronomic traits under contrasting water supply. These findings may explain the importance of Q.ICD.11.…”
Section: Discussionmentioning
confidence: 94%
“…The short arm of chromosome 2A, where Ppd-A1 is located, is a hot spot for genes which have minor effects on multiple yield-related traits. Several previous genome-wide association studies have identified specific regions on chromosome 2A associated with quantitative trait loci (QTL) that influence both physiological and agronomic traits in wheat (Guo et al 2017 ; Shi et al 2017 ; Wolde et al 2019 ; Gahlaut et al 2019 ; Hu et al 2020 ; Kaur et al 2020 ; Pshenichnikova et al 2021 ; Ding et al 2022 ). Our analysis is based on the correlation of variants of Ppd-1 with agronomic traits without controlling for population structure in a set of cultivars with diverse genomic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that T. timopheevii is adapted to the ecological conditions of a humid cool climate (Wheats of the World, 1976). Previously, it was shown that a fragment of 2A chromosome of S29 contains a large cluster of QTLs associated with the physiological response to drought in the region of the centromere and the molecular marker Xgwm339 (Pshenichnikova et al 2021). This region is included in the introgression and may be relevant to reaction to water availability.…”
Section: Discussionmentioning
confidence: 99%